Systematic Review of Invasive Acinetobacter Infections in Children - Jia Hu; Joan L Robinson (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Clinicians are generally familiar with Acinetobacter as an etiological agent for serious nosocomial infections in intensive care units. However, there are no previous reviews of the full spectrum of invasive infections in children.